Dying for growth: global inequality and the health of the poor (Cambridge, MA, 2000)
"Dying For Growth is a deeply intelligent, thoroughly researched analysis of global health and inequality at the end of the 20th Century. It is a book of passion and courage that does not simply make indignant claims, but rather provides solid evidence of a causal relationship between failures of the current development paradigm and worsening poverty and human suffering. Written by a team of experienced health practitioners, social scientists and development workers, the volume speaks from both the heart and the mind about the urgent need to prioritize social justice and universal health improvements. Dying For Growth is a 'must-read' for all citizens and activists commited to meaningful change, who believe that health is central to the dignity of the person." --James Orbinski, President, Médecins Sans Frontières (MSF) International Council, MSF was awarded the 1999 Nobel Peace Prize--